Psychobiological risk factors for insomnia and depressed mood among hospital female nurses working shifts - Bennaroch, Kochav; Shochat, Tamar (Frontiers in Sleep, 2023)
Introduction: Despite a vast body of knowledge on the associations between insomnia and depression, and although women and shift workers are at high risk for each of these conditions separately, common psychobiological risk factors for developing insomnia and depressed mood concomitantly in high-functioning shift-working female nurses have yet to be investigated within a comprehensive framework. This study examines the contribution of shift work (disruption of circadian rhythms), stress, analytical rumination, and morningnesseveningness on the development of insomnia and depressed mood among female hospital nurses.We sought to assess the severity and prevalence of insomnia symptoms and depressed mood among hospital shift-working compared with day-working nurses; to examine associations between psychobiological risk factors with insomnia and depressed mood; and to develop a conceptual psychobiological model to describe their co-occurrence among hospital nurses.Methods: Using a cross-sectional design, we recruited female hospital nurses, shift workers (SW) and day workers (DW: only morning shifts), and assessed them for insomnia, depressed mood, stress, analytical rumination, and morningness-eveningness through validated selfadministered questionnaires delivered online. Using structural equation modeling (SEM), we assessed common pathways between psychobiological factors affecting insomnia and depressed mood.Results: 448 nurses completed electronic questionnaires. SW nurses (n=358) compared with DW nurses (n =90) had significantly higher rates of insomnia and depressed mood. SW nurses also reported significantly higher severity of insomnia, depressed mood, stress, and a tendency to eveningness compared with DW nurses. A positive linear relationship was found between insomnia and depressed mood in both SW and DW nurses. SEM showed that shift work contributed directly to insomnia and indirectly to depressed mood. The overall model showed a good fit between the empirical and the conceptual psychobiological model proposed in the study [χ (1)=.16, p=.69, CFI=.99, RMSEA=0.0001].Discussion: We found that SW nurses who reported high levels of stress and eveningness are at significantly greater risk for both insomnia symptoms and depressed mood. Findings provide the groundwork in creating a conceptual psychobiological model to examine the co-occurrence of insomnia and depressed mood phenomena in hospital nurses. This research is an important first step towards the development of interventions aimed at improving nurses' health.